2022
DOI: 10.21203/rs.3.rs-2288620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil-targeted Mn3O4 nanozyme treats myocardial ischemia reperfusion injury by scavenging reactive oxygen species

Abstract: Background: The core pathophysiological process of myocardial ischemia reperfusion injury (MIRI) is the excessive reactive oxygen species (ROS) production (including •O2-, H2O2, •OH) in the injured areas. Manganese tetroxide (Mn3O4) nanozymes are capable of scavenging multiple ROS, but whether they are applicable in MIRI is unclear. Rat IgG-modified liposomes can be specifically phagocytosed by activated neutrophils. Activated neutrophils can penetrate the vascular barrier and infiltrate into the inflamed myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Additionally, in rapidly evolving conditions such as stroke, the need to treat patients as quickly as possible would likely preclude the use of any strategy involving ex vivo manipulation of cells. Direct, in vivo targeting of WBC has been reported to promote nanoparticle delivery and penetration into tumors, among other organs. , Additionally, targeting of pulmonary intravascular leukocytes has been reported as a therapeutic strategy in treatment of mouse models of acute respiratory distress syndrome by our group and others. This approach represents a significant step forward in WBC-based drug delivery. It has been reported that intercellular adhesion molecule 1 (ICAM) is expressed on the surface of many activated WBC, including monocytes and neutrophils .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, in rapidly evolving conditions such as stroke, the need to treat patients as quickly as possible would likely preclude the use of any strategy involving ex vivo manipulation of cells. Direct, in vivo targeting of WBC has been reported to promote nanoparticle delivery and penetration into tumors, among other organs. , Additionally, targeting of pulmonary intravascular leukocytes has been reported as a therapeutic strategy in treatment of mouse models of acute respiratory distress syndrome by our group and others. This approach represents a significant step forward in WBC-based drug delivery. It has been reported that intercellular adhesion molecule 1 (ICAM) is expressed on the surface of many activated WBC, including monocytes and neutrophils .…”
Section: Introductionmentioning
confidence: 98%
“…Direct, in vivo targeting of WBC has been reported to promote nanoparticle delivery 32 and penetration 33 into tumors, among other organs. 34 , 35 Additionally, targeting of pulmonary intravascular leukocytes has been reported as a therapeutic strategy in treatment of mouse models of acute respiratory distress syndrome by our group and others. 36 39 This approach represents a significant step forward in WBC-based drug delivery.…”
Section: Introductionmentioning
confidence: 99%